Buckling analysis of three-phase CNT/polymer/fiber functionally graded orthotropic plates: Influence of the non-uniform distribution of the oriented fibers on the critical load. (15th November 2020) - Bacciocchi, Michele
Highlights: General power-law functions are introduced to characterize the graded distribution of the fibers. The validity of the proposed approach to study graded structures is proven by comparison tests. A multi-scale approach is presented to analyze three-phase composites. Several mechanical configurations and boundary conditions are investrigated. The uniaxial and biaxial critical buckling loads are affected by the non-uniform properties of the layers. Abstract: The current paper aims to analyze the influence on the critical buckling loads of the non-uniform distribution of the oriented fibers along the thickness direction of three-phase CNT/polymer/fiber functionally graded orthotropic plates. The various plies of the laminated plates are reinforced by both carbon nanotube (CNT) particles and conventional oriented straight fibers. The orthotropic features of such layers are provided by the reinforcing fibers which are functionally graded (FG) along the thickness coordinate. In the literature, CNTs represent generally the sole reinforcing phase and are assumed aligned and graded in the thickness direction. Here, instead, CNTs are randomly oriented and uniformly scattered in the matrix, whose properties are further improved by aligned, graded, straight and oriented fibers. A general power-law function is introduced to define the non-uniform features instead of the usual patterns presented in the literature (such as FG-X and FG-O), which can be included in the proposed approach as particular cases. The current methodology is tested through the comparison with the results available in the literature. The validation procedure is carried out for two-phases composites, considering also CNTs as straight and aligned reinforcing fibers, characterized by both uniform and graded properties. Several boundary conditions are also analyzed and verified. As proven by the numerical results illustrated in the paper, the variation of the through-the-thickness distribution of the fiber volume fraction is able to change noticeably the value of both uniaxial and biaxial critical buckling loads of arbitrarily restrained thin and thick plates. This effect should be considered in the manufacturing process and in the mechanical analysis of these structures.